Description of a new species of the leafhopper genus Reticuluma Cheng & Li, 2005 (Hemiptera: Cicadellidae: Penthimiini) from China with a key to species - Xu, Tielong; Yu, Zhou; Dai, Renhuai; Yang, Maofa (Zootaxa, 2020)
A new species Reticuluma bipennata sp. nov. from China is described and illustrated, and can be distinguished from other Reticuluma by the aedeagal shaft with a pair of wing-shaped processes on the lateral margin. A key to all species of the genus based on the features of males and a map showing the geographic distribution of the genus are given.